Efforts To Improve Alignment Ability Through Problem Solving Method - Italia, Italia; Subekti, Tamsur; Mudmaina, Mudmaina; Bahtiar, Yuyun (SCHOOLAR: Social and Literature Study in Education, 2025)
The aim of this research is motivated by low Mathematics scores, especially in the aspect of Calculating Mixed Whole Number Operations. Based on the analysis of the formative tests of Class V students at Public Elementary School 04 Babat Banyuasin, out of 13 students, only 3 students, or 23% achieved completeness, the rest were still below the school's KKM, namely ≥ 75. The method in this research used the Classroom Action Research (CAR) method. The aim of the Classroom Action Research that the researchers conducted was to find out how much the use of teaching aids and problem solving methods can increase student motivation as a result of the learning improvements that have been implemented. This research was carried out in two cycles, namely cycle I and cycle II. In cycle I the average score was 77.85 with learning completeness of 62% or out of 13 students only 8 children achieved completeness and 5 children did not. This shows an increase from pre-cycle to Cycle I and according to the researchers, this is not satisfactory. After progressing to the second cycle stage, the average score was 83.23 with 85% completeness, or of the 13 children who achieved completeness, 11 children and 2 children did not complete it. Thus it can be concluded that the use of teaching aids and problem solving methods can increase students' learning motivation.